The Effect of Bacteriophage Preparations on Intracellular Killing of Bacteria by Phagocytes - Ewa Jończyk-Matysiak; Marzanna Łusiak-Szelachowska; Marlena Kłak; Barbara Bubak; Ryszard Międzybrodzki; Beata Weber-Dąbrowska; Maciej Żaczek; Wojciech Fortuna; Paweł Rogóż; Sławomir Letkiewicz; Krzysztof Szufnarowski; Andrzej Górski (Journal of Immunology Research)
Intracellular killing of bacteria is one of the fundamental mechanisms against invading pathogens. Impaired intracellular killing of bacteria by phagocytes may be the reason of chronic infections and may be caused by antibiotics or substances that can be produced by some bacteria. Therefore, it was of great practical importance to examine whether phage preparations may influence the process of phagocyte intracellular killing of bacteria. It may be important especially in the case of patients qualified for experimental phage therapy (approximately half of the patients with chronic bacterial infections have their immunity impaired). Our analysis included 51 patients with chronic Gram-negative and Gram-positive bacterial infections treated with phage preparations at the Phage Therapy Unit in Wroclaw. The aim of the study was to investigate the effect of experimental phage therapy on intracellular killing of bacteria by patients’ peripheral blood monocytes and polymorphonuclear neutrophils. We observed that phage therapy does not reduce patients’ phagocytes’ ability to kill bacteria, and it does not affect the activity of phagocytes in patients with initially reduced ability to kill bacteria intracellularly. Our results suggest that experimental phage therapy has no significant adverse effects on the bactericidal properties of phagocytes, which confirms the safety of the therapy.